Male fertility: a review of the publications from January - March 2021 - D. S. Rogozin (Вестник урологии, 2021)
The article provides an overview of the most significant publications on the topic of male infertility. The main selection criteria were the practical significance of the article, as well as the impact factor of the journal in which it was published, according to the SCImago Journal Rank (SJR). As a result, a list of 10 works published in the first quarter (January - March) of 2021 was formed. The review included articles related to the following issues: sperm DNA fragmentation, the use of testicular spermatozoa in ART programs (assisted reproductive technologies), advanced paternal age, the role of the human papillomavirus for male fertility, hormonal modulation by clomiphene, the risk of birth defects in children in ART programs, andrological examination of patients with CFTR gene mutations. And also, an analysis of the new clinical guidelines of the American Urological Association (AUA) was carried out.